JURI OPI (OLIMPIADE PELITA INDONESIA) MAGIC 5.0 INSTITUT BISNIS DAN TEKNOLOGI PELITA INDONESIA - Irman, Mimelientesa; Anton, Anton; Yusrizal, Yusrizal; Suharti, Suharti; Fadrul, Fadrul (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2024)
The form of this activity is OPI (Indonesian Pelita Olympics) Magic 5.0 at the Pelita Indonesia Institute of Business and Technology which was organized by BEM IBT Pelita Indonesia with the theme "Millennial Advancement Generating Innovative Creativity". Various competitions were held at this Olympics, including; Web Design Competition, Bazaar Competition, Poster Design, 4D Mading Competition and Accounting Olympiad. The Accounting Competition itself is expected to be a forum for channeling competitive skills in the field of accounting and introducing the Indonesian Institute of Business and Technology in general, and the Accounting major in particular to high school/vocational school students.